Evaluasi WMS Menggunakan PIECES dan Analisis Gap pada Gema Insani Press - Erlangga Rahimi; Farhatul Atqiya; Shelly Pramudiawardani (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2026)
A Warehouse management system (WMS) plays a crucial role in supporting inventory management and the distribution of goods. Evaluating the system’s Service quality from the users’ perspective is necessary to ensure it meets the company’s needs. This study aims to evaluate the WMS at Gema Insani Press using the PIECES Framework and Gap Analysis. The study employs a descriptive quantitative approach with saturation sampling involving 20 WMS users. Data were collected through questionnaires and observations, then analyzed using validity and reliability tests, PIECES analysis, and Gap Analysis. The results showed that all dimensions received good ratings with actual scores ranging from 3.76 to 3.89. The Efficiency dimension received the highest score (3.89), while the Information dimension received the lowest (3.76). The Gap Analysis revealed that the Information dimension had the largest gap (0.18), making it a priority for system development. The research results indicate that the integration of the PIECES Framework and Gap Analysis is effective for evaluating quality and determining priorities for improving warehouse Information systems.Keywords: Warehouse management system; PIECES Framework; Gap Analysis; Information System Evaluation; Warehousing. AbstrakWarehouse management system (WMS) berperan penting dalam mendukung pengelolaan persediaan dan distribusi barang. Evaluasi kualitas layanan sistem dari perspektif pengguna diperlukan untuk memastikan kesesuaiannya dengan kebutuhan perusahaan. Penelitian ini bertujuan mengevaluasi WMS di Gema Insani Press menggunakan PIECES Framework dan Analisis Gap. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan sampling jenuh yang melibatkan 20 pengguna WMS. Data dikumpulkan melalui kuesioner dan observasi, kemudian dianalisis menggunakan uji validitas, reliabilitas, analisis PIECES, dan Analisis Gap. Hasil menunjukkan seluruh dimensi memperoleh penilaian baik dengan nilai aktual 3,76–3,89. Dimensi Efficiency memperoleh nilai tertinggi (3,89), sedangkan Information terendah (3,76). Analisis Gap menunjukkan dimensi Information memiliki kesenjangan terbesar (0,18) sehingga menjadi prioritas pengembangan sistem. Hasil penelitian menunjukkan bahwa integrasi PIECES Framework dan Analisis Gap efektif untuk mengevaluasi kualitas serta menentukan prioritas peningkatan sistem informasi pergudangan.